Comparative Efficacy of Artemether-Lumefantrine and Dihydroartemisinin-Piperaquine for the Treatment of Uncomplicated Malaria in Ugandan Children - Yeka, Adoke; Mulebeke, Ronald; Kigozi, Ruth; Bosco, Agaba; Kyambadde, Paul; Senzoga, Joseph; Conrad, Melissa; Rosenthal, Philip J. (The Journal of infectious diseases, 2019)
In Uganda, artemether-lumefantrine (AL) and dihydroartemisinin-piperaquine (DHA-PQ) showed excellent treatment efficacy for uncomplicated malaria in prior trials. Because the frequency of resistance to artemisinins and piperaquine is increasing in Southeast Asia and the prevalence of Plasmodium falciparum polymorphisms associated with resistance has changed, we reassessed treatment efficacies at 3 sites in Uganda.